2014
DOI: 10.1186/1744-8603-10-26
|View full text |Cite
|
Sign up to set email alerts
|

Open access: academic publishing and its implications for knowledge equity in Kenya

Abstract: Traditional, subscription-based scientific publishing has its limitations: often, articles are inaccessible to the majority of researchers in low-and middle-income countries (LMICs), where journal subscriptions or one-time access fees are cost-prohibitive. Open access (OA) publishing, in which journals provide online access to articles free of charge, breaks this barrier and allows unrestricted access to scientific and scholarly information to researchers all over the globe. At the same time, one major limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Open access is beneficial for research universities (their rankings and impact measures improve); for funders whose missions of creating and sharing knowledge are realised; for the research process which sees efficiencies, immediacy and transparency; and for the development imperatives of universities and societies at large for which the scholarly resources of universities are made available to all. 9 Open access is essential for visibility and has proven valuable for citations: in a meta-study of 35 studies surveyed, 27 showed a citations advantage (the percentage increase ranged from 45% to as high as 600%). 10 For those from less developed countries, the effect is more profound: the influence of free access on citations has been shown to be twice as large for the poorer countries in the developing world compared to richer countries, as measured by per capita gross national income.…”
Section: The Value Propositionmentioning
confidence: 99%
“…Open access is beneficial for research universities (their rankings and impact measures improve); for funders whose missions of creating and sharing knowledge are realised; for the research process which sees efficiencies, immediacy and transparency; and for the development imperatives of universities and societies at large for which the scholarly resources of universities are made available to all. 9 Open access is essential for visibility and has proven valuable for citations: in a meta-study of 35 studies surveyed, 27 showed a citations advantage (the percentage increase ranged from 45% to as high as 600%). 10 For those from less developed countries, the effect is more profound: the influence of free access on citations has been shown to be twice as large for the poorer countries in the developing world compared to richer countries, as measured by per capita gross national income.…”
Section: The Value Propositionmentioning
confidence: 99%
“…Open access helps researchers as readers by opening up access to articles that their libraries do not subscribe to. One of the great beneficiaries of open access may be users in developing countries, where currently some universities find it difficult to pay for subscriptions required to access the most recent journals [12][13][14]. Some schemes exist for providing subscription scientific publications to those affiliated to institutions in developing countries at little or no cost.…”
Section: Discussionmentioning
confidence: 99%
“…Opening access to publications, and particularly adopting a ‘green’ archiving policy, is essential for improving visibility of non-mainstream science countries and academic disciplines with limited funding and a small number of indexed journals (1415). Gold open access, which was adopted as a priority for British academic and research institutions in 2012, relied on the advances in academic disciplines of interest to the global community, well-established publishing industry, and substantial research funding available for British and European researchers at that time (16).…”
Section: Preferable Access Optionsmentioning
confidence: 99%